Just do it: Embodied experiences improve taekwondo athletes` sport performance - Ottoboni, G.; Giusti, R.; Gatta, A.; Symes, E.; Tessari, A. (Sensoria - A journal of mind, brain and culture, 2013)
According to the embodied perspective, cognitive processes are entwined with sensory-motor processes (Shapiro, 2011). The present study investigates the implications of such a perspective in the sport domain. We provided a group of athletes with sessions of embodied relaxation exercises designed to increase their body awareness, in addition to standard Taekwondo training while a control group of athletes received an extra period of standard training. Sport performance was assessed for the two groups by means of Taekwondo exams. Athletes performed better on the Taekwondo exam with the addition of embodied relaxation training and this effect was influenced by the number of sessions each athlete attended. The positive effect of embodied relaxation training on taekwondo performance suggests that embodied cognition may have an applied influence in the domain of sports.